Analysis of student’s mathematical thinking in solving HOTs problems viewed from mathematics anxiety - Wedastuti, Ni Ketut; Faradiba, Surya Sari (SAINTIS Publishing, 2023)
This study aims to describe students' mathematical thinking processes in terms of math anxiety. The method used in this research is descriptive qualitative. Data collection techniques were carried out through tests, documentation and interviews. The determination of the subject used a purposive sampling technique by taking 5 student level subjects who had very high, high, medium, low, and very low levels of math anxiety. The results showed that in the process of working on the test instrument in the form of HOTS questions, subjects with very low levels of anxiety were able to solve the first and second problems correctly. In the entry phase, the subject fulfills the I know, I want, and introduce rubik. And in the attack phase it fulfills the rubik's try, may be, and why. In the review phase it only fulfills the Rubik's check, and does not meet the rubik reflect and extend. This can be seen from the results of work that does not use a general formula.